Shadowcaster eaudiobook - Chima, Cinda Williams (Shattered Realms, 2017)
From New York Times bestselling author Cinda Williams Chima, this is a thrilling story of the unfathomable costs of war, the allure of dark magic, and two principled and conflicted characters drawn together despite everything they stand to lose. Alyssa ana'Raisa, the reluctant princess heir to the Gray Wolf throne of the Fells, feels more comfortable striking with a sword than maneuvering at court. After a brush with death, Lyss goes on the offensive, meaning to end the war that has raged her whole life. If her gamble doesn't pay off, she could lose her queendom before she even ascends to the throne. Across enemy lines in Arden, young rising star Captain Halston Matelon is being sent on ever more dangerous assignments. Between the terrifying rumors of witches and wolfish warriors to the north and his cruel king at home, Hal is caught in an impossible game of life and death. Lyss and Hal's intricately linked fates become inseparable when they fall under the shadow of a new enemy—a force that threatens to extinguish the last rays of hope in the Shattered Realms.